Last visit was: 23 Jul 2024, 12:59 It is currently 23 Jul 2024, 12:59
Close
GMAT Club Daily Prep
Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track
Your Progress

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History
Not interested in getting valuable practice questions and articles delivered to your email? No problem, unsubscribe here.
Close
Request Expert Reply
Confirm Cancel
SORT BY:
Date
Math Revolution GMAT Instructor
Joined: 16 Aug 2015
Posts: 10133
Own Kudos [?]: 17050 [17]
Given Kudos: 4
GMAT 1: 760 Q51 V42
GPA: 3.82
Send PM
Retired Moderator
Joined: 19 Oct 2018
Posts: 1868
Own Kudos [?]: 6663 [3]
Given Kudos: 705
Location: India
Send PM
GMAT Club Legend
GMAT Club Legend
Joined: 03 Jun 2019
Posts: 5312
Own Kudos [?]: 4245 [2]
Given Kudos: 161
Location: India
GMAT 1: 690 Q50 V34
WE:Engineering (Transportation)
Send PM
Math Revolution GMAT Instructor
Joined: 16 Aug 2015
Posts: 10133
Own Kudos [?]: 17050 [0]
Given Kudos: 4
GMAT 1: 760 Q51 V42
GPA: 3.82
Send PM
Re: A function f(x) satisfies 2f(x)+3f(1-x)=x^2. What is the expression of [#permalink]
Expert Reply
=>

We have \(4f(x)+6f(1-x)=2x^2\) when we multiply the equation in the original condition by \(2\).

If we substitute \(x\) by \(1-x,\) then we have \(2f(1-x)+3f(x) = (1-x)^2.\)

If we multiply the equation by \(3\), we have \(6f(1-x)+9f(x) = 3(1-x)^2.\)

If we subtract equations \([4f(x)+6f(1-x)=2x^2] - [6f(1-x)+9f(x) = 3(1-x)^2]\), then we have \(-5f(x) = 2x^2 – 3(1-x)^2, -5f(x) = 2x^2 - 3(1-2x+x^2), -5f(x) = 2x^2 - 3 + 6x - 3x^2, -5f(x) = -x^2 + 6x – 3\) or \(f(x) = (\frac{1}{5})(x^2-6x+3).\)

Therefore, the answer is D.
Answer: D
Intern
Intern
Joined: 28 Jan 2019
Posts: 17
Own Kudos [?]: 5 [0]
Given Kudos: 2
GMAT 1: 730 Q47 V42
Send PM
Re: A function f(x) satisfies 2f(x)+3f(1-x)=x^2. What is the expression of [#permalink]
MathRevolution, could you please explain why you chose those operations: substituting, multiplying by 3, etc.?
Intern
Intern
Joined: 18 May 2021
Posts: 14
Own Kudos [?]: 0 [0]
Given Kudos: 4
Send PM
Re: A function f(x) satisfies 2f(x)+3f(1-x)=x^2. What is the expression of [#permalink]
MathRevolution wrote:
=>

We have \(4f(x)+6f(1-x)=2x^2\) when we multiply the equation in the original condition by \(2\).

If we substitute \(x\) by \(1-x,\) then we have \(2f(1-x)+3f(x) = (1-x)^2.\)

If we multiply the equation by \(3\), we have \(6f(1-x)+9f(x) = 3(1-x)^2.\)

If we subtract equations \([4f(x)+6f(1-x)=2x^2] - [6f(1-x)+9f(x) = 3(1-x)^2]\), then we have \(-5f(x) = 2x^2 – 3(1-x)^2, -5f(x) = 2x^2 - 3(1-2x+x^2), -5f(x) = 2x^2 - 3 + 6x - 3x^2, -5f(x) = -x^2 + 6x – 3\) or \(f(x) = (\frac{1}{5})(x^2-6x+3).\)

Therefore, the answer is D.
Answer: D

In this part If we substitute \(x\) by \(1-x,\) then we have \(2f(1-x)+3f(x) = (1-x)^2.\)
What made you want to substitute (1-x) in for x?
avatar
Intern
Intern
Joined: 21 Jul 2022
Posts: 2
Own Kudos [?]: 0 [0]
Given Kudos: 2
Location: India
Send PM
Re: A function f(x) satisfies 2f(x)+3f(1-x)=x^2. What is the expression of [#permalink]
nick1816 wrote:
\(2f(x)+3f(1-x)=x^2.\) .......(1)


put x=1-x, we get

\(2f(1-x)+3f(x)=(1-x)^2.\) ........(2)

Multiply equation (1) by 2 and equation (2) by 3 and subtract both equations

we'll get

f(x)= \(\frac{(x^2 -6x +3)}{5}\)


MathRevolution wrote:
[GMAT math practice question]

A function \(f(x)\) satisfies \(2f(x)+3f(1-x)=x^2.\) What is the expression of \(f(x)\)?

\(A. \frac{(x^2 +6x +3)}{7}\)

\(B. \frac{(x^2 -6x +3)}{7}\)

\(C. \frac{(x^2 -6x +1)}{3}\)

\(D. \frac{(x^2 -6x +3)}{5}\)

\(E. \frac{(x^2 +6x +3)}{5}\)


Posted from my mobile device
avatar
Intern
Intern
Joined: 21 Jul 2022
Posts: 2
Own Kudos [?]: 0 [0]
Given Kudos: 2
Location: India
Send PM
Re: A function f(x) satisfies 2f(x)+3f(1-x)=x^2. What is the expression of [#permalink]
Sid116 wrote:
nick1816 wrote:
\(2f(x)+3f(1-x)=x^2.\) .......(1)


put x=1-x, we get

\(2f(1-x)+3f(x)=(1-x)^2.\) ........(2)

Multiply equation (1) by 2 and equation (2) by 3 and subtract both equations

we'll get

f(x)= \(\frac{(x^2 -6x +3)}{5}\)


MathRevolution wrote:
[GMAT math practice question]

A function \(f(x)\) satisfies \(2f(x)+3f(1-x)=x^2.\) What is the expression of \(f(x)\)?

\(A. \frac{(x^2 +6x +3)}{7}\)

\(B. \frac{(x^2 -6x +3)}{7}\)

\(C. \frac{(x^2 -6x +1)}{3}\)

\(D. \frac{(x^2 -6x +3)}{5}\)

\(E. \frac{(x^2 +6x +3)}{5}\)


Posted from my mobile device
Director
Director
Joined: 06 Dec 2021
Posts: 520
Own Kudos [?]: 547 [2]
Given Kudos: 737
Location: India
Concentration: Technology, International Business
GPA: 4
WE:Human Resources (Telecommunications)
Send PM
A function f(x) satisfies 2f(x)+3f(1-x)=x^2. What is the expression of [#permalink]
2
Kudos
A simple and elegant way to solve function questions
A function f(x) satisfies 2f(x)+3f(1−x)=x^2. What is the expression of f(x)?
Lets assume that x = 1/2 (why 1/2 because in that case x = 1-x = 1/2)
this way we get f(x) = f(1-x)
so substituting x = 1/2 in the given condition
2f(1/2) + 3f(1/2) = 1/4
5f(1/2) = 1/4
or f(1/2) = 1/20
Now put x = 1/2 to check which option gives f(1/2) = 1/20
only expression given in option D produces f(1/2) = 1/20
Answer D
GMAT Club Bot
A function f(x) satisfies 2f(x)+3f(1-x)=x^2. What is the expression of [#permalink]
Moderator:
Math Expert
94592 posts